2024
DOI: 10.1021/acssuschemeng.4c01274
|View full text |Cite
|
Sign up to set email alerts
|

On Sustainability Aspects of the Synthesis of Five-Membered Cyclic Carbonates

Federico Mundo,
Sylvain Caillol,
Vincent Ladmiral
et al.

Abstract: The synthesis of cyclic carbonates, substrates gaining growing interest due to their broad spectrum of applications, is analyzed from a Green Chemistry perspective. Extensive research has been carried out on the synthesis of these substances, which are of interest especially for the preparation of so-called non-isocyanate polyurethanes (NIPUs). Often, the renewability of the raw materials, derived for instance from carbon dioxide, diols, urea, or alkyl carbonates, is taken into account, without considering sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 87 publications
(107 reference statements)
0
2
0
Order By: Relevance
“…E factor) due to the CO 2 -based synthetic pathway for the cyclic carbonate monomer (5CC), which has recently been identified as more sustainable than the dimethylcarbonate pathway. 57 Moreover, the bio-based content was still higher than previously reported water-induced self-blown NIPU obtained from CO 2 -based 5CC. 28 Therefore, our work represents a significant step toward sustainable biomass-rich self-blown isocyanate-free polyurethane foams.…”
Section: Discussionmentioning
confidence: 72%
“…E factor) due to the CO 2 -based synthetic pathway for the cyclic carbonate monomer (5CC), which has recently been identified as more sustainable than the dimethylcarbonate pathway. 57 Moreover, the bio-based content was still higher than previously reported water-induced self-blown NIPU obtained from CO 2 -based 5CC. 28 Therefore, our work represents a significant step toward sustainable biomass-rich self-blown isocyanate-free polyurethane foams.…”
Section: Discussionmentioning
confidence: 72%
“…Ultrasonication can promote cavitation phenomena, thus causing hot spots in the solution media featuring high local temperature and pressure, causing the formation of free radical species, which can trigger chemical reactions . Notably, it appears that hydroxide (•OH) and superoxide (HO 2 –•) radicals produced during the acoustic cavitation process in lignin suspensions can promote lignin oxidation, leading to its chemical cross-linking and subsequent polymerization. ,, Indeed, extensive oxidation occurs for long sonication times or in a strong oxidizing agent during the ultrasound treatment. , From NMR analysis and the experiments of chemical degradation (Figure S-2B), it can be shown that no significant cross-linking is achieved due to ultrasonication in the hybrid synthesis. As reported by previous studies, this might be due to the short sonication time as well as the low lignin concentration because of its progressive addition to the batch.…”
Section: Resultsmentioning
confidence: 99%